Autophagic Recycling Plays a Central Role in Maize Nitrogen Remobilization. Issue 5 (5th May 2015) - Li, Faqiang; Chung, Taijoon; Pennington, Janice G.; Federico, Maria L.; Kaeppler, Heidi F.; Kaeppler, Shawn M.; Otegui, Marisa S.; Vierstra, Richard D.
Abstract : Characterization of maize autophagy through detailed transcriptome studies and phenotypic and 15 N-partitioning analyses of atg12 mutants reveal a central role for autophagy in nitrogen remobilization. Abstract: Autophagy is a primary route for nutrient recycling in plants by which superfluous or damaged cytoplasmic material and organelles are encapsulated and delivered to the vacuole for breakdown. Central to autophagy is a conjugation pathway that attaches AUTOPHAGY-RELATED8 (ATG8) to phosphatidylethanolamine, which then coats emerging autophagic membranes and helps with cargo recruitment, vesicle enclosure, and subsequent vesicle docking with the tonoplast. A key component in ATG8 function is ATG12, which promotes lipidation upon its attachment to ATG5. Here, we fully defined the maize ( Zea mays ) ATG system transcriptionally and characterized it genetically through atg12 mutants that block ATG8 modification. atg12 plants have compromised autophagic transport as determined by localization of a YFP-ATG8 reporter and its vacuolar cleavage during nitrogen or fixed-carbon starvation. Phenotypic analyses showed that atg12 plants are phenotypically normal and fertile when grown under nutrient-rich conditions. However, when nitrogen-starved, seedling growth is severely arrested, and as the plants mature, they show enhanced leaf senescence and stunted ear development. Nitrogen partitioning studies revealed that remobilization is impaired in atg12 plants, which significantly decreases seed yield and nitrogen-harvest index. Together, our studies demonstrate that autophagy, while nonessential, becomes critical during nitrogen stress and severely impacts maize productivity under suboptimal field conditions.